Governo aberto, lobby e qualidade legislativa: estudo de caso sobre a regulamentação do Marco Civil da Internet - Felipe Lélis Moreira (2017)
The objective of the present work was to investigate the potential of using the Crowdlaw platforms as lobbying spaces and Legistics´ tools for the improvement of the quality of the legislation that comes from the Executive Power. Thus, a presentation of the concept of Open Government was made relationing it with the Crowdlaw platforms. Later, we demonstrated that the civic participation at the online legislative process can be considered a lobby practice, which is not regulated in Brazil and involves a series of prejudices that we aimed to deconstruct exploring it and proving that lobby is a Constitutional right that can be practiced by any individual. Next, we introduced the Legistics, a science that have the dialogue with the recipients of a norm as a nuclear value for a quality of legislative communication and consequently of the legislation. Finally, it was developed a case study on the Brazils internet bill of rights´ process of regulation in which it was possible to prove the existence of potential benefits in the use of public consultations, but which were not explored in the case analyzed, that had the political factor as the main obstacle.